2017
DOI: 10.1155/2017/9529257
|View full text |Cite
|
Sign up to set email alerts
|

Use of Integrative Medicine in the United States Military Health System

Abstract: Integrative medicine (IM) is a model of care which uses both conventional and nonconventional therapies in a “whole person” approach to achieve optimum mental, physical, emotional, spiritual, and environmental health, and is increasingly popular among patients and providers seeking to relieve chronic or multifactorial conditions. The US Department of Defense (DoD) shows particular interest in and usage of IM for managing chronic conditions including the signature “polytrauma triad” of chronic pain, traumatic b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 111 publications
0
12
0
Order By: Relevance
“…41 Integrative medicine, a holistic model of care which aims to selectively combine the exclusively evidence-based complementary and alternative therapies into conventional medicine, 42 has risen in popularity in recent years among patients and medical providers for the relief of chronic or multifactorial conditions such as CNCP. 43 It is a combination of medical treatments such as acupuncture, massage relaxation techniques, healing touch, etc. 44,45 Clinical studies have shown that acupuncture is a reasonable effective option for multiple chronic pain conditions.…”
Section: Is Who Analgesic Ladder Appropriate To Cncp?mentioning
confidence: 99%
See 1 more Smart Citation
“…41 Integrative medicine, a holistic model of care which aims to selectively combine the exclusively evidence-based complementary and alternative therapies into conventional medicine, 42 has risen in popularity in recent years among patients and medical providers for the relief of chronic or multifactorial conditions such as CNCP. 43 It is a combination of medical treatments such as acupuncture, massage relaxation techniques, healing touch, etc. 44,45 Clinical studies have shown that acupuncture is a reasonable effective option for multiple chronic pain conditions.…”
Section: Is Who Analgesic Ladder Appropriate To Cncp?mentioning
confidence: 99%
“…46 There is a rising interest in using acupuncture for CNCP instead of reliance on opioid analgesics. 43 The substantial basic knowledge development on pain and its therapies has led to the CNCP guidelines being updated, 14,[18][19][20][21]47 while the WHO three-step analgesic ladder has remained unchanged.…”
Section: Is Who Analgesic Ladder Appropriate To Cncp?mentioning
confidence: 99%
“…Complementary and ancillary interventions may enhance the success of efforts to promote better physical and mental health, and quality of life for military service members (Madsen, Vaughan & Koehlmoos, 2017). Among ancillary programs, many involve outdoor activities (Stigsdotter et al, 2011) such as sports (Caddick, Smith & Phoenix, 2014;Caddick, Smith & Phoenix, 2015;Marchand et al, 2018), horticulture (Gorman & Cacciatore, 2017;Lehmann, Detweiler & Detweiler, 2018), nature adventure (Gelkopf et al, 2013;Hyer et al, 1996), equine and other animal therapies (Fine & Beck, 2015), and spending time in nature (Poulsen, Stigsdotter & Davidsen, 2018;Poulsen, Stigsdotter & Refshage, 2015;Wagenfeld, Roy-Fisher & Mitchell, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A total of 23 integrative therapies across 15 modalities are reported in use across the MHS, ranging from clinical standards such as cognitive-behavioral therapy, to body-based techniques such as chiropractic and yoga, to various mindfulness and meditative exercises. 18 Similarly, like the situation in the VHA, these therapies are not standardized across treatment facilities, and efforts to increase access are frequently patient-driven. 18,19 Taken together, this comparison of the VHA and the MHS shows multiple opportunities for acupuncture to serve as a point of crossagency capacity building, knowledge sharing, and care standardization.…”
Section: Introductionmentioning
confidence: 99%
“…18 Similarly, like the situation in the VHA, these therapies are not standardized across treatment facilities, and efforts to increase access are frequently patient-driven. 18,19 Taken together, this comparison of the VHA and the MHS shows multiple opportunities for acupuncture to serve as a point of crossagency capacity building, knowledge sharing, and care standardization. While the DoD has provided leadership for several bridging efforts, including the DVCIPM, DVBIC, the ATACS program, and the Pain Management Task Force, the VHA holds significant resources in the Integrative Health Coordinating Center.…”
Section: Introductionmentioning
confidence: 99%